#TITLE_ALTERNATIVE# - SATRIO WIRAWAN (NIM 10302023), YUDHO
According to the big bang theory of the universe, the object which we called ÃƒÂ‚Ã‚Â“quasarsÃƒÂ‚Ã‚Â” are having large redshift. The distance to these objects could be determined with Hubble law. Where large redshift corresponds with larger distance. When quasarÃƒÂ‚Ã‚Â’s light have reached earth, the energy will be lower than the energy when emitted by the source. So we need correction of wavelength to determined quasarÃƒÂ‚Ã‚Â’s magnitude in rest frame. In such a way with Sloan Digital Sky Survey (SDSS) photometric data which resulted from observation using five bands filter u, g, r, i, z. When the data used for modeling quasar variability, we could not use the magnitude data in particular band and then comparing with another quasar at the same band. Because when redshift differs, its meant that the light we received originate from different wavelength. The results show that most quasar which having large redshift, shifted too far from SDSS filter interval. So that λ0 are much smaller than λeff which used for observation. The interval characterized by Full Width Half Maximum (FWHM) of each filter. Temporarily, we could not used such results and also for λ0 which located between two filter so that itÃƒÂ‚Ã‚Â’s not included in one of the filterÃƒÂ‚Ã‚Â’s interval.